2021
DOI: 10.1002/ncp.10741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrition status of very preterm infants in neonatal intensive care units using different growth indicators

Abstract: Background  Nutrition status of very preterm infants in the neonatal intensive care unit (NICU) is strongly associated with postnatal growth. This study aimed to develop indicators of nutrition status using growth data of very preterm infants during hospitalization. Methods The data of 596 newborns from eight NICUs were retrospectively analyzed. Inclusion criteria were birth at <32 weeks’ gestation, NICU admission ≤24 h after delivery, and length of hospital stay ≥28 days. Three indicators were evaluated: (ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Small for gestational age or suitable for gestational age infants might have different postnatal growth outcomes [ 40 ]. To facilitate the establishment of nutritional guidelines in the TP, clinicians must choose a reasonable evaluation indicator in combination with individual characteristics to objectively assess the nutritional status of preterm infants [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small for gestational age or suitable for gestational age infants might have different postnatal growth outcomes [ 40 ]. To facilitate the establishment of nutritional guidelines in the TP, clinicians must choose a reasonable evaluation indicator in combination with individual characteristics to objectively assess the nutritional status of preterm infants [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 3 4 For the catch-up growth of very low birth weight (VLBW) infants, regular comprehensive checkups to monitor growth and provide early intervention to achieve normal growth are essential. 5 Developed countries such as Canada, the United States, Australia, and Japan have conducted high-risk follow-up clinics to improve neonatal outcomes and accumulate long-term growth and development. 6 7 …”
Section: Introductionmentioning
confidence: 99%
“…At present, an increasing number of studies focus on dynamic EUGR, which refers to the change in body weight Z -score related to birth status. In 2021, a multicenter study from Jiangsu Province, China, found that the change in weight Z -score was closely related to the time to regain birth weight, birth weight, and gestational age ( 7 ). To reduce the growth failure of preterm infants after birth, sufficient attention should be paid to the time variable to regain birth weight in NICUs.…”
mentioning
confidence: 99%